A Scale for Assessing Degree of Strength of Client Feeling - Trainor, Katherine; Pilloud, Louise; Mahrer, Alvin R.; Stalikas, Anastassios; Boissoneault, Marc (Canadian Journal of Counselling and Psychotherapy, 2011)
Reviews of counseling research indicate that there are no instruments explicitly designed to assess degree of strength of client feeling. Based on a conceptual analysis of related measures, a graduated series of clinical trials culminated in the development of a Strength of Client Feeling Scale for assessing four levels: neutral, low, moderate, and strong. Very low Spearman coefficients between the Strength of Client Feeling Scale and the Experiencing Scale on client-centred, rational-emotive, and experiential sessions indicate that the two scales assess independent constructs. The Strength of Client Feeling Scale is introduced as useful for selected avenues of counseling research.